Surface mass balance modelling of the Juneau Icefield highlights the potential for rapid ice loss by the mid-21st century - Ryan Nicholas Ing; Jeremy Charles Ely; Julie Margaret Jones; Bethan Joan Davies (Journal of Glaciology)
Plateau icefields are large stores of fresh water, preconditioned to enhanced mass loss due to their gently sloping accumulation areas. Accurate modelling of their mass balance is therefore crucial for sea-level rise projections. Here, we use the COupled Snowpack and Ice surface energy and mass-balance model in PYthon (COSIPY) to simulate historical and future mass balance of the Juneau Icefield, Alaska – a high elevation (>1200 m) plateau icefield. We force the model with dynamically downscaled climate simulations, for both past and future (RCP 8.5) conditions. The icefield's mass balance decreased from a mean of −0.22 ± 0.38 m w.e. a−1 (1981–2019) to −1.52 ± 0.27 m w.e. a−1 (2031–2060), with many glaciers shifting from positive to negative mass balances at the start of the 21st century. This mass loss is attributed to projected rising air temperatures and reduced snowfall, causing the equilibrium line altitude to rise and triggering albedo and melt-elevation feedbacks. These processes exacerbate melt, potentially leading to increased glacier disconnections at icefalls.